A Review of Theories Relevant to E-banking Usage Continuance - Harasis, Ahmad Ali; Rasli, Amran (International Review of Management and Marketing, 2016)
The study emphasises on extending a model about personality attributes as a moderator on the relationship between contentment and the persistent utilisation of electronic banking services (e-banking). Furthermore, the recommended model expounds the dependent aspects based on the technology continuance theory (TCT) which mould the e-banking continuance intention. This paper takes forward the evolving corpus of research on e-banking by stretching the theoretic precincts of the e-banking continuance model, and contributes to research on e-banking. Keywords: E-banking; big five personality attributes; satisfaction; continuance intention JEL Classification: G21